Design and analysis of planar microwave antenna system with beam self-alignment - Ou, Zhaocong (2018)
With the rapid development in the field of Aerospace and the limited spectrum resources, there is a crucial need for modern satellite communications (SATCOM) systems with the feature of low-cost, high gain and the capability of beam self-alignment. Retrodirective antenna (RDA) has the characteristic of reflecting an incident wave towards the source direction without any prior information on the source location and the complex digital signal processing. It is based on phase conjugation techniques with fast-track features and it is cost-effective. This dissertation summarized the current study of different types of retrodirective antenna arrays, analyzed and discussed the advantages and disadvantages of them. A new allanalogue phase conjugation circuit solution is introduced which is compatible with an integrated broadband global area network (BGAN) product, BGAN radio module (BRM), this new front-end system can directly track phase-modulated signals with level as low as -130 dBm. Moreover, this paper makes frequency planning with both input and output of mixer are RF signals, which is a new thought of using the traditional frequency planning method. The fundamental of achieving this new SATCOM RDA array system are given, and some important characteristics such as spurious emission, chain gain planning and noise figure are analyzed in this work, then the block diagram along with the schematic diagram of the phase conjugation circuit are shown. The result of this system shows that the noise figure of RX end is about 2.064 dB in the worst case and TX end of this front-end circuit can achieve a transmission gain larger than 40 dB, which is eligible for the SATCOM array system.